Urgensi Belajar dan Bersujud dalam QS. al- ‘Alaq Ayat 1 dan 19: Kajian Munasabah Al-Qur’an - Ihsan Nurmansyah; Sherli Kurnia Oktaviana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Basically humans have two main devices, namely the heart and mind. But in reality, some humans prioritize reason in the learning process, while others prioritize the heart. Therefore, this study aims to examine how the Qur'an responds and answers these problems, as contained in QS. al-'Alaq verses 1 and 19. The method used is the method of munasabah al-Qur'an between opening and closing surahs. The results of this study are the first and opening verses of QS. al-'Alaq ordered reading. Reading means learning and activating the mind to educate the intellectual. The command to study and read is not enough, it must be complemented by the order to prostrate and draw closer to Allah. Sujud means submission and obedience to Allah and a lot of use of the heart to educate spiritually. A lot of reading and study should also be a lot of prostration. People who read intensively, but do not prostrate, will transform into smart and intelligent people, but are arrogant, arrogant and arrogant. By intensively reading and prostrating, you will become closer to Allah and close to your fellow human beings. That is the harmonious munasabah between the opening and closing verses in QS. al-'Alaq.